Efficacy of regular prophylaxis with a plasma-derived von Willebrand factor/factor VIII concentrate with a 1:1 activity ratio in reducing heavy menstrual bleeding in girls/women with von Willebrand diseaseAJOG Global Reports at a Glance - Csongor Kiss; Zoltan Boda; Claudia Djambas Khayat; Ana Boban; Leonid Dubey; Robert F. Sidonio Jr (AJOG Global Reports, 2025)
Background: Heavy menstrual bleeding is the dominant symptom in girls/women with von Willebrand disease (VWD), affecting ∼80 to 90%. Female patients with VWD are typically diagnosed later than males, despite the disproportionate impact of heavy menstrual bleeding. Although heavy menstrual bleeding has a substantial impact on patients, it is commonly undertreated in part because of the potential multifactorial causes in young girls/women, imprecise definition, and exclusion of this bleeding type as an indication for prophylaxis in previous studies. The WIL-31 study showed that prophylaxis with wilate (a plasma-derived von Willebrand factor/factor VIII concentrate with a 1:1 activity ratio) is highly efficacious in reducing bleeding rates in adults and children with VWD of all types. The impact of wilate prophylaxis on heavy menstrual bleeding was evaluated as an exploratory endpoint since it was not included as part of the primary endpoint. Objective(s): To investigate the efficacy of regular prophylaxis with wilate in reducing the incidence of heavy menstrual bleeding in girls/women with VWD who had previously been treated on-demand. Study design: WIL-31 (NCT04052698) was a prospective, non-controlled, international, multicenter Phase 3 trial that enrolled male/female patients, aged ≥ 6 years old with VWD. Prior to entering the WIL-31 study, all patients received on-demand treatment with a von Willebrand factor-containing product during a 6-month, prospective, observational, run-in study (WIL-29). Patients in WIL-31 received wilate prophylaxis 2–3 times per week at a dose of 20–40 IU/kg for 12 months. Prophylaxis was not tailored to time with menstruation. Heavy menstrual bleeding was defined as any menstrual bleed that impeded the ability to perform daily activities during menstrual periods. Criteria for heavy menstrual bleeding included changing pads more frequently than hourly, menstrual bleeding lasting 7 or more days, or the presence of clots > 1 cm, combined with a history of flooding or a Pictorial Blood Assessment Chart score ≥ 185. Results: Of the 33 patients evaluated in the study, 14 (42%) were female, of whom 5 (15%) were of childbearing age (13–43 years old). One of these had VWD type 1, the other 4 had VWD type 3. Prophylaxis with wilate reduced the mean annualized heavy menstrual bleeding rate by 75% compared with on-demand treatment (2.4 vs 9.7 in WIL-31 and WIL-29, respectively). During 6 months of on-demand treatment, all 5 female patients experienced at least 1 heavy menstrual bleed, whereas during 12 months of prophylaxis, 3 (60%) experienced no heavy menstrual bleeding episodes. During on-demand treatment, 5 patients experienced 26 heavy menstrual bleeding episodes, 3 (12%) of which required additional treatment. Under prophylaxis, 2 patients experienced 12 heavy menstrual bleeding episodes, of which only 1 (8%) impeded daily activity and none required additional treatment. Conclusions: In these exploratory analyses, wilate prophylaxis given 2–3 times a week without menstruation coordination was efficacious in reducing heavy menstrual bleeding in girls/women with VWD compared with on-demand treatment. Long-term prophylaxis has the potential to play a major role in improving the care and reducing the disease burden for girls/women with VWD.